Improving the Quality of Higher Education Institution through Well-Traced Accounting Education Graduates - *, Siswandari; *, Susilaningsih; Sumaryati, Sri; Muchsini, Binti (Sebelas Maret University, 2016)
The objective of this research is to improve the quality of higher education institution, namely: the Study Program of Accounting Education through well-traced graduates from the view of the alumni of the Study Program of Accounting Education â the Faculty of Teacher Training and Education Sebelas Maret University and their users. The population of this research was all of the alumni. Its samples consisted of 860 alumni of the class of 2000s. The data of research were collected through observation, documentation, and focus group discussion with the users of alumni and APRODIKSI (Association of the Study Programs of Accounting Education). They were then analyzed by using the descriptive statistics. The results of research are as follows: 1) 88% of the alumni are satisfied with the education and learning process management at the Study Program of Accounting Education, Sebelas Maret University. 2) Based on the view of its alumni, the waiting time to get the first job is short; 60% of the graduates get their first job within three months following their graduation; 25% of them get their first job from three months to six months following their graduation, and the rest get their job after six months following their graduation. 3) Only 30% of the graduates have a job which is relevant to their field of study â they become Accounting teachers, or instructors in some related courses and staffs at the Ministry of Education and Culture. Furthermore, 70% of the graduates have varied positions namely: Directors in manufacturing companies, Financial Managers, Marketing Managers, staffs of financial institutions such as banks or leasing companies. Moreover, only 5% of them become entrepreneurs. 4) The first salary that they earn is decent enough, but only 10% of the graduates get the first salary in the amount of more than IDR 3,000,000 and 90% get the first salary in the amount between IDR 1,000,000 â 3,000,000. In addition, from the view of the users of alumni, they feel fairly satisfied with the alumniâs performance, and they expect that the institution will enhance the âflexible attitudesâ of their graduates in facing certain situations which require wise solutions to solve the existing problems.Â Â